Pengaruh Citra Merek, Kualitas Produk, Harga dan Kesadaran Merek terhadap Keputusan Pembelian Mobil Honda Mobilio di Kota Semarang - Audita Devita Laksmitadewi; Saryadi Saryadi; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2016)
The car is a land transportation that loved by many people. Like Indonesia whichgrow in crowded people causes Indonesia’s families choose car as their main transportation,mainly Low MPV. One of popular automotive industry is Honda. Honda produce Low MPV,named Mobilio. Since launched at January 2014, Mobilio can get the second position of LowMPV, which it below Toyota Avanza.This research aim is to find the influence of brand image, product quality, price andbrand awareness to buying decision of Honda Mobilio. This research is include inexplanatory and using 96 respondent as research sample from Mobilio’s consument inSemarang. The sample was taken by using nonprobability sampling and purposive sampling.Data were collected using questioner and was analyzed using simple linear regression,multiple linear regression, correlation coefficient, determination coefficient, t test and F test.The questioner was tested by using validity and reliability test.The result of this research showed that there positive impact and significant betweenbrand image, product quality, price and brand awareness towards buying decision of HondaMobilio in Semarang either partially or simultaneously. The variable brand image is thegreatest effect on buying decision of Honda Mobilio in Semarang than product quality, priceand brand awareness. Base on the result of this research, it can be concluded that there isinfluence of brand image, product quality, price and brand awareness to buying decision ofHonda Mobilio. It means that improving brand image, product quality, price and brandawareness can also increasing buying decision of Honda Mobilio.Advice can be given for Honda and the need to increase product quality be done byrepairing and doing inovation, also increase brand awareness be done by intensive promotionso buying decision of Mobilio will be increase.